The Process of Working with Claims in The Quality Management System of An Enterprise of The Radio-Electronic Industry. - Yu. Cheremukhina, Yu.; A. Baranova, I.; V. Muravev, V.; V. Kurenkov, V.; V. Myskov, D. (International Journal of Engineering and Technology, 2018)
The article is devoted to the requirements of the quality standard GOST R ISO 9001-2015 to work with claims in the radio electronic industry. Reclamation management as a quality management system process is the key to a successful transition to the new version of GOST R ISO 9001-2015. The main stages of the complaint handling process and the indicators for evaluating its effectiveness have been determined. Â